Indigenous Governance and Social Cohesion: A Marsialapari-Based Pentahelix Collaboration Model for Community Development - Lubis, Anggia Sari; et al. (European Journal of Social Science Education and Research, 2026)
This study examines the role of indigenous governance through the Mandailing local wisdom of Marsialapari in strengthening social cohesion and participatory collaboration within the Pentahelix framework in Medan, Indonesia. Drawing on perspectives of social capital, participatory governance, and indigenous knowledge systems, the study conceptualizes a Marsialapari-based Pentahelix model integrating academia, business, government, community, and media through the values of solidarity, reciprocity, mutual assistance, and collective responsibility embedded in local tradition. Employing a mixed-method sequential explanatory design, data were collected from 350 women entrepreneurs and community actors through surveys, focus group discussions, and interviews, and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) alongside qualitative interpretation. The findings reveal that effective communication and self-confidence significantly strengthen Marsialapari-based Pentahelix collaboration, while social interaction shows a weaker influence. The study further demonstrates that indigenous collaboration practices positively contribute to social cohesion, participatory engagement, community resilience, and collective empowerment. Readiness for social change also strengthens the relationship between Marsialapari-based collaboration and community development outcomes. The study contributes theoretically by repositioning local wisdom as a form of indigenous governance and social capital within collaborative governance frameworks. Practically, the findings emphasize the importance of integrating culturally grounded values into participatory governance to strengthen sustainable and socially resilient communities.